2016
DOI: 10.15244/pjoes/60417
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Arylsulfatase to Contamination of Soil by Heavy Metals

Abstract: Contamination of soils by heavy metals is a severe problem because of disturbances caused in the functioning of the soil and the whole ecosystem. Therefore, the aim of our research was to determine the influence of contamination of soil by zinc, copper, nickel, cadmium, and lead on the activity of arylsulfatase. A novel element of the study is a comparison of the response of arylsulfatase to five heavy metals in three soils with two pH ranges: 7.0 and 5.5. The studies were carried out under laboratory conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Soil pH is one of the very important factors that are considered to evaluate the effect of pollutants on the activity of soil microorganisms, however, it is very difficult to separate the effect of heavy metal stress on soil microbial populations from that due to pH changes (García-Gil et al, 2013). Changing soil pH to an acidic level due to the soil management effect may intensify the heavy metal effect further (Wyszkowska et al, 2016). The decreasing pH leads to the increased bioavailability of Cu, Cd, Zn and Pb in soil (Aponte et al, 2020), which results in higher heavy metal toxicity for microorganisms and inhibition of enzyme activities.…”
Section: Effect Of Soil Physicochemical Properties and Heavy Metal Interactions On Soil Microbial And Enzyme Activitymentioning
confidence: 99%
“…Soil pH is one of the very important factors that are considered to evaluate the effect of pollutants on the activity of soil microorganisms, however, it is very difficult to separate the effect of heavy metal stress on soil microbial populations from that due to pH changes (García-Gil et al, 2013). Changing soil pH to an acidic level due to the soil management effect may intensify the heavy metal effect further (Wyszkowska et al, 2016). The decreasing pH leads to the increased bioavailability of Cu, Cd, Zn and Pb in soil (Aponte et al, 2020), which results in higher heavy metal toxicity for microorganisms and inhibition of enzyme activities.…”
Section: Effect Of Soil Physicochemical Properties and Heavy Metal Interactions On Soil Microbial And Enzyme Activitymentioning
confidence: 99%
“…The inhibition of urease activity by crude petroleum has been reported elsewhere. 13,31,32 Margesin 33 found that soil urease activity was stimulated by diesel while inhibited by PAHs. The results in this study further indicated a correlation between the type and concentration of pollutant and its effect on urease activity.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
“…Crude petroleum consists of linear and branched chain alkanes, cycloalkanes and aromatics as dominant constituents, and also contains small amounts of nitrogen-, oxygen-and sulfur-containing compounds, such as pyridine, phenol and thioether, respectively. 1 Some components, mainly polycyclic aromatic hydrocarbons are hazardous xenobiotics, 2 showing potential teratogenic, carcinogenic and mutagenic activities, 3 and threaten human health when accumulated in crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is very difficult to separate the effect of heavy metal stress on soil microbial populations from that due to pH changes (García Gil et al, 2013). Acidic pH levels may intensify the heavy metal effect further (Wyszkowska et al, 2016). The low pH leads to the increased bioavailability of Cd and Pb in soil (Humberto et al, 2020), which results in higher heavy metal toxicity for microorganisms and inhibition of enzyme activities.…”
Section: Tablementioning
confidence: 99%